ChemInform Abstract: Tautomerization of 2, 6‐Lutidines in the Presence of B(C6F5)3 Using Catecholborane as a Precatalyst. Issue 30 (July 2016) - Zheng, Junhao; Fan, Xiaoting; Zhou, Benyu; Li, Zhen Hua; Wang, Huadong
Abstract: The reaction of 2‐methylpyridines (I) with B(C6 F5 )3 leads to borylated pyridinium derivatives (III), which are used for the Suzuki—Miyaura coupling to afford 2‐benzylpyridines (V).